Ruthenium complexes show potent inhibition of AKR1C1, AKR1C2, and AKR1C3 enzymes and anti-proliferative action against chemoresistant ovarian cancer cell line - Kljun, Jakob; Pavlič, Renata; Hafner, Eva; Lipec, Tanja; Moreno-Da Silva, Sara; Tič, Primož; Turel, Iztok; Büdefeld, Tomaž; Stojan, Jure; Rižner, Tea Lanišnik (Frontiers in Pharmacology, 2022)
In this study we present the synthesis, kinetic studies of inhibitory activity towards aldo-keto reductase 1C (AKR1C) enzymes and anticancer potential towards chemoresistant ovarian cancer of 10 organoruthenium compounds bearing diketonate (1-6) and hydroxyquinolinate (7-10) chelating ligands with the general formula [(η6-p-cymene)Ru(chel)(X)]n+ where chel represents the chelating ligand and X the chlorido or pta ligand. Our studies show that these compounds are potent inhibitors of the AKR enzymes with an uncommon inhibitory mechanism, where two inhibitor molecules bind to the enzyme in a first fast and reversible step and a second slower and irreversible step. The binding potency of each step is dependent on the chemical structure of the monodentate ligands in the metalloinhibitors with the chlorido complexes generally acting as reversible inhibitors and pta complexes as irreversible inhibitors. Our study also shows that compounds 1-9 have a better anti-proliferative and anti-migration action on the chemoresistant ovarian cancer cell line COV362 compared to carboplatin and similar effects to cisplatin.